Home » Aptitude » Quadratic Equation » Question
  1. Form a quadratic equation whose one root is 3 - √5 and the sum of roots is 6
    1. x2 − 6x + 4 = 0
    2. x2 + 6x + 4 = 0
    3. x2 − 6x − 4 = 0
    4. None of these
Correct Option: A

Given : - Sum of the roots ( k1 + k2 ) = 6
One root k1 = 3 - √5
∴ the other root k2 = 6 - ( 3 - √5) = 3 + √5
∴ Product of roots k1k2 = ( 3 - √5 ) ( 3 + √5 )
product of roots = 9 - 5 = 4
Hence , the required equation is x2 - (sum of the roots)x + (product of roots) = 0
⇒ x2 - 6x + 4 = 0.



Your comments will be displayed only after manual approval.